1999
DOI: 10.1093/jn/129.1.77
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Used for the Production of Yogurt Inactivate Carcinogens and Prevent DNA Damage in the Colon of Rats

Abstract: Lactic acid-producing bacteria prevent carcinogen-induced preneoplastic lesions and tumors in rat colon. Because the mechanisms responsible for these protective effects are unknown, two strains of lactic acid bacteria, Lactobacillus delbrueckii ssp. bulgaricus 191R and Streptococcus salivarius ssp. thermophilus CH3, that are used to produce yogurt, were investigated in vitro and in vivo to elucidate their potential to deactivate carcinogens. Using the "Comet assay" to detect genetic damage, we found that L. bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 26 publications
2
56
0
3
Order By: Relevance
“…Cells were isolated from the colon with proteinase K as described by Wollowski et al [1999]. The colons were flushed with prewarmed RPMI 1640 medium, filled with the digestion solution (50 U/ml proteinase K in RPMI 1640), and incubated at 378C for 30 min.…”
Section: Isolation Of Liver and Colon Cellsmentioning
confidence: 99%
“…Cells were isolated from the colon with proteinase K as described by Wollowski et al [1999]. The colons were flushed with prewarmed RPMI 1640 medium, filled with the digestion solution (50 U/ml proteinase K in RPMI 1640), and incubated at 378C for 30 min.…”
Section: Isolation Of Liver and Colon Cellsmentioning
confidence: 99%
“…Beneficial bacterial strains include Lactobacillus acidophilus [11], L. casei [15], Bifidobacterium longum [37], B. infantis [16] and some other lactic acid bacteria. Two bacterial species, L. bulgaricus and Streptococcus thermophilus, are used as a starter culture for the fermentation of milk to make yogurt, and various reports regarding the antitumor effects of these two lactic acid bacteria have been published: the anti-mutagenic activity of yogurt [4], the protective effect of L. bulgaricus against DNA damage [12,42,44], and the preventive role of yogurt against colon cancer [7,36]. Of note, Shackeford et al reported that drinking milk fermented by L. bulgaricus and S. thermophilus altered the metabolism of DMH and shifted the colon tumor distribution toward the anus [36].…”
Section: Discussionmentioning
confidence: 99%
“…There are abundant reports on the beneficial effects of yogurt on human health [1], and many investigators have suggested that the consumption of fermented dairy products, including yogurt, elicits anti-tumor effects [12,42,44]. However, the reported anti-tumor effects of yogurt are inconsistent, and these inconsistencies may have arisen from the different bacterial strains and culture conditions and different experimental protocols used in the studies -Original- [36,42].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that tea decreases mammary and colon tumor induction, and milk potentiates these inhibiting effects [20]. Dairy products and milk were also reported to inhibit tumor growth [21] and particularly yoghurt inactivates carcinogens and prevents DNA damage [22]. Cow's milk was also suggested in older infants for its anticarcinogenic effects [23].…”
Section: Discussionmentioning
confidence: 99%